2023
DOI: 10.1002/jia2.26107
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the values and preferences regarding the use of injectable pre‐exposure prophylaxis to prevent HIV acquisition

Abstract: Introduction: Pre-exposure prophylaxis (PrEP) is an important HIV prevention option. Two randomized trials have provided efficacy evidence for long-acting injectable cabotegravir (CAB-LA) as PrEP. In considering CAB-LA as an additional PrEP modality for people at substantial risk of HIV, it is important to understand community response to injectable PrEP. We conducted a systematic review of values, preferences and perceptions of acceptability for injectable PrEP to inform global guidance. Methods: We searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 85 publications
(280 reference statements)
1
11
0
Order By: Relevance
“…Our updated model has been parameterized using recent data from a PrEP cohort study conducted among pregnant and postpartum women in South Africa, which shows reasonable oral PrEP uptake but limited adherence and continuation [5,7,15]. In this context, CAB-LA could potentially be very important, reducing HIV incidence in PBW by around 40%, and reducing vertical transmission by around 24% – a reflection of both greater acceptability of injectable prevention methods [22–24] and superior efficacy [9]. Offering a choice of CAB-LA and oral PrEP would lead to the greatest PrEP uptake (consistent with the effect of choice in family planning [25]), but the impact on HIV transmission would not differ materially from offering CAB-LA alone.…”
Section: Discussionmentioning
confidence: 95%
“…Our updated model has been parameterized using recent data from a PrEP cohort study conducted among pregnant and postpartum women in South Africa, which shows reasonable oral PrEP uptake but limited adherence and continuation [5,7,15]. In this context, CAB-LA could potentially be very important, reducing HIV incidence in PBW by around 40%, and reducing vertical transmission by around 24% – a reflection of both greater acceptability of injectable prevention methods [22–24] and superior efficacy [9]. Offering a choice of CAB-LA and oral PrEP would lead to the greatest PrEP uptake (consistent with the effect of choice in family planning [25]), but the impact on HIV transmission would not differ materially from offering CAB-LA alone.…”
Section: Discussionmentioning
confidence: 95%
“…A previously published review assessed values and preferences for long-acting injectable PrEP; however, most studies included were published on or before October 2021, before regulatory approval of the first long-acting ARV for use as PrEP, CAB-LA [36]. Authors found broad interest in and overall preference for LAIs and highlighted the perceived benefits of discretion and less frequent dosing.…”
Section: Discussionmentioning
confidence: 99%
“…1 University of Pennsylvania, Philadelphia, Pennsylvania, USA; 2 Bridge HIV at the San Francisco Department of Public Health, San Francisco, California, USA; 3 Research Institute for Health Sciences, Chiang Mai University, Chiang Mai, Thailand; 4 University of Alabama at Birmingham, Birmingham, Alabama, USA;…”
Section: A U T H O R S ' a F F I L I At I O N Smentioning
confidence: 99%